2008
DOI: 10.1007/s00216-008-1993-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative effect of Bacteroides thetaiotaomicron extracts: superoxide dismutase identification

Abstract: Bacteroides thetaiotaomicron, a bowel anaerobic commensal, seems to release enzymes detoxifying reactive oxygen species according to our recent work. This opportunistic pathogen would be beneficial in the case of an inflammatory process. To explore its role after an oxidative or nutritive stress, six to seven separate experiments were performed. The bacteria were grown on media restricted in growth factors or supplemented with bile. Their viability was checked after surface protein extraction. The extracts und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…However, superoxide dismutase is not detected in these extracts. As previously described (Hochart-Behra et al, 2008), chaperonin proteins were also found such as chaperone protein DnaK (c1), SCO1/SenC chaperone. Glutamate decarboxylase (s1), is another stress protein previously widely described in our extracts (Hochart-Behra et al, 2008).…”
Section: The Interaction Benefited the Intestine Bacteria And The Yeast Population Was Stablesupporting
confidence: 57%
See 4 more Smart Citations
“…However, superoxide dismutase is not detected in these extracts. As previously described (Hochart-Behra et al, 2008), chaperonin proteins were also found such as chaperone protein DnaK (c1), SCO1/SenC chaperone. Glutamate decarboxylase (s1), is another stress protein previously widely described in our extracts (Hochart-Behra et al, 2008).…”
Section: The Interaction Benefited the Intestine Bacteria And The Yeast Population Was Stablesupporting
confidence: 57%
“…The same process was applied to B. thetaiotaomicron ATCC 29741 and K. marxianus S-02-5 grown concomitantly and separately, in the same conditions as for their co-culture. After centrifugation, followed by three successive washes in Ringer medium ¼, the pellets of pure B. thetaiotaomicron ATCC 29741 and of pure K. marxianus S-02-5 and of B. thetaiotaomicron ATCC 29741 co-culturing with K. marxianus S-02-5 were placed in agitation in mild detergent solution containing 7 mM 3-[(3-cholamidopropyl) dimethylammonio]-1 propanesulfonate, 0.5 mM tris(hydroxymethyl) aminomethane hydrochloride at pH 6.8 (Serva, Heidelberg, Germany) -a cholic acid derivative -overnight at 4 C, as previously described for B. thetaiotaomicron (Hochart-Behra et al, 2008 at a rate of 4 ml of extraction solution per g of microorganisms. The suspensions were centrifuged and the supernatant was filtered 0.22 m (Millipore corporation, Bedford, MA, USA), and assayed for protein content (Hochart-Behra et al, 2008).…”
Section: Interactions Inter-species: B Thetaiotaomicron Atcc 29741 Vs K Marxianus S-02-5mentioning
confidence: 99%
See 3 more Smart Citations